Valores, atitudes e comportamentos gerenciais requeridos pelo processo de globalização e as diretrizes para as ações de desenvolvimento de recursos humanos - Bittencourt, Andrea Gomes (1998)
The process of globalization is now reality, altering the relationship between nations, society and organizations. Globalization ofthe economy radically changes the relation of man with the productive and social spheres, raising fundamental aspects of the essence of present transformations, that justify apparently inexplicable tendencies. Strong and swift changes that demand both of men as well as of organizations the hability to adapt in way never experienced before, are the only certainties of present times. This promotes the simultaneous appearance of several managerial tendencies of organizational changes in the Brazüian business scenario. This work intends to promote reflexion on the effects that ongoing changes have caused in the code of managerial values, attitudes and behavior required by the organizations, as well as on the new role to be carried out by the área of Human Resources Development.